A comparative assessment of policy induced diffusion pathways for utility scale solar PV: case study of Indonesia - Syafina, Paramastri; Oluleye, Gbemi (Frontiers in Sustainable Energy Policy, 2024)
Lack of effective policies hinder the uptake of Utility-scale solar PV, even though they are projected to play a pivotal role in achieving Indonesia’s 2050 net-zero energy target. This study seeks to identify a cost-effective pathway to increase the capacity of utility-scale solar PV in Indonesia through supportive policies that ensure equitable cost distribution between the government and industry. A novel Market Penetration Optimization Model is developed and applied in simulation mode to assess existing policies, and optimization mode to determine new policy recommendations and compare three policy induced diffusion pathways. Results show that current price-based policies are insufficient to stimulate growth in the solar PV market, only covering approximately 13% of the investment cost required by the industry. Thus, necessitating a reactivation of Feed-in-Tariffs. The optimal tariffs rates required range from 0.39 to 1.47 cents /kWh for the most economic pathway during the initial ten-year post-construction period. The Innovation Diffusion Theory-based pathway necessitates the lowest initial investment cost while yielding the highest revenue from electricity sales, demonstrating its superior cost-effectiveness compared to both the supply-based and linear pathways. This study enriches the literature by exploring the financial implications of policy induced diffusion pathways.